2006
DOI: 10.1002/pssb.200672515
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure Raman study on type‐I germanium clathrate

Abstract: Raman scattering measurements of the type-I Ge clathrtate, Ba 8 Ge 43 , have been performed at 1 bar and room temperature, and under high-pressures up to 22 GPa. Because of vacancies which exist in Ba 8 Ge 43 , the Raman spectrum at 1 bar was found to be different from that of Si clathrate. Low-frequency vibrational modes associated with Ba atoms were found around 35 -75 cm -1 and the Ge-framework Raman bands were observed around 80 -150 cm -1 comparable to the typical clathrate Ba 8 Si 46 . For these regions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…However, the pressures applied in the Ba 8 Si 46 study were much higher ͑ϳ1.7-20 GPa͒ than used here for Ba 8 Ga 16 Ge 30 ͑0.9 GPa͒. In a recent study of Ba 8 Ge 43 ᮀ 3 it was likewise observed that all modes shift to higher energies with applied pressure, 32 but again the applied pressures were higher ͑2.6-22 GPa͒ compared with the pressure used in this study.…”
Section: Inelastic Neutron Scatteringsupporting
confidence: 41%
“…However, the pressures applied in the Ba 8 Si 46 study were much higher ͑ϳ1.7-20 GPa͒ than used here for Ba 8 Ga 16 Ge 30 ͑0.9 GPa͒. In a recent study of Ba 8 Ge 43 ᮀ 3 it was likewise observed that all modes shift to higher energies with applied pressure, 32 but again the applied pressures were higher ͑2.6-22 GPa͒ compared with the pressure used in this study.…”
Section: Inelastic Neutron Scatteringsupporting
confidence: 41%
“…[9]). The high-pressure behavior of filled clathrates was studied, e.g., for Ba 8 Si 46 [10], Ba 7.5 Si 45 [11], Ba 8 Ge 43 [12], or Rb 6. 15 Si 46 [13], where pressure-induced amorphization (PIA) and polyamorphic transition were observed (for a review, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Récemment, Fukushima et al ont réalisé une étude comparative de Ba 8 Si 46 et Ba 8 Ge 43 X 3 , ce dernier comportant dans son réseau d'accueil des lacunes ordonnées (paragraphe 3.1) impliquant la présence d'atomes de germanium triplement liés seulement[149]. Les spectres de diffusion Raman des deux clathrates sont très proches pour les fréquences inférieures à 200 cm À1 , mais diffèrent nettement pour les plus hautes fréquences en raison de la quasi-disparition dans le spectre du clathrate lacunaire de modes de vibrations nettement visibles pour le clathrate stoechiométrique.…”
unclassified